Considering local immunity for innovative immunomodulatory approaches: pulmonary sepsis as a use case - Vernay, Emilie; Cerrato, Elisabeth; Santinon, François; Monard, Céline; Perez, Pauline; Allantaz, Florence; Lukaszewicz, Anne-Claire; Llitjos, Jean-François (Frontiers in Immunology, 2025)
Owing to faster identification of sepsis and improvement of patient management, most septic patients now survive the early phase of sepsis. Therefore, one of the major challenges in sepsis management today is to identify those patients at risk and propose effective personalized therapy. The complexity of the mechanisms involved in the septic immune response and its dysregulation is reflected in the diversity of immune profiles among sepsis patients. It is now well recognized that this heterogeneity is a major obstacle to stratifying patients based on their susceptibility to secondary infections. Since sepsis can originate from different anatomical sites, some studies have investigated their impact to decipher the heterogeneity. They concluded that the site of infection affects patient outcomes and leads to different immune alterations. This narrative review focuses on pulmonary sepsis to highlight the importance of studying organ response directly with local immune cells. Understanding the persistent dysregulation within the lung, whether it involves pulmonary immune cells or other lung components, is critical. Some studies have already examined the remodeling and loss of functionality of alveolar macrophages after the initial insult. Ongoing research is also investigating the impact of imbalances in other lung players, such as epithelial cells or the microbiota, on susceptibility to pulmonary reinfection.